2021
DOI: 10.36376/bmj.v8i3.173
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan wanita usia subur (wus) tentang covid-19 dan perilaku pencegahannya pada masa pandemi di kecamatan kuta utara badung

Abstract: Virus Corona (COVID-19) menjadi masalah kesehatan dunia dan telah menginfeksi secara global termasuk Indonesia yang mengakibatkan tingginya angka mortalitas dan morbiditas. Pengetahuan yang baik dan perilaku hidup bersih dan sehat sebagai upaya pencegahan penyebaran COVID-19.  Peran seorang wanita dalam keluarga memegang peran yang sangat penting salah satunya untuk menjaga kesehatan seluruh anggota keluarga agar tetap sehat terlebih lagi dalam masa pandemi COVID-19. Tujuan penelitian ini adalah untuk mengetah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Coronavirus adalah keluarga besar virus yang menyebabkan penyakit mulai dari gejala ringan sampai berat. Coronavirus yang diketahui dapat menyebabkan penyakit yang menimbulkan gejala berat seperti Middle East Respiratory Syndrome (MERS) dan Severe Acute Respiratory Syndrome (SARS).Coronavirus Disease 2019 (COVID-19) adalah penyakit jenis baru yang belum pernah diidentifikasi sebelumnya pada manusia 1 .…”
Section: Pendahuluanunclassified
“…Coronavirus adalah keluarga besar virus yang menyebabkan penyakit mulai dari gejala ringan sampai berat. Coronavirus yang diketahui dapat menyebabkan penyakit yang menimbulkan gejala berat seperti Middle East Respiratory Syndrome (MERS) dan Severe Acute Respiratory Syndrome (SARS).Coronavirus Disease 2019 (COVID-19) adalah penyakit jenis baru yang belum pernah diidentifikasi sebelumnya pada manusia 1 .…”
Section: Pendahuluanunclassified
“…10 Every resident must be able to maintain health by complying with health protocols to help break the chain of disease transmission in people of all ages and walks of life, including Women of Reproductive Age, who play an important role in the family and can meet the needs of all family members. 11 Women of Reproductive Age are women aged 15 to 49 years with unmarried, married, or widowed status who are included in the reproductive age category 12 . Low knowledge about risks and how to stop transmission of the virus is a factor that can affect Women of Reproductive Age's awareness of preventing COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…11 Factors that influence COVID-19 prevention behavior in WUS are sociodemographic factors consisting of a person's age, education, and occupation. The results of research on the people of Paya Bujok Blang Pase Village, Langsa City showed that there was a relationship between age, education, Democratic Republic of the Congo, there was no statistically significant difference in the effect of education level on women's knowledge, attitudes, and practices for controlling transmission of COVID-19 in Democratic Congo, women with higher levels of education were not found to always show increased knowledge, attitudes, or practice of appropriate strategies for prevention and control of…”
mentioning
confidence: 99%